(untitled) (Contemporary Society and Politics Journal, 2023)
Abstract This article examines the leadership of women in Islam from the perspective of Muhammadiyah. The theme has always generated both support and opposition among the Muslim community. The central point of debate regarding women’s leadership in Islam revolves around a hadith narrated by Abu Bakrah, stating that a community will not prosper if led by a woman. The result of this research is that Muhammadiyah has decided that women are allowed to become leaders, starting from school principals, directors, or even presidents. They believe there is no explicit text that clearly prohibits women from being leaders. Regarding the hadith, Muhammadiyah interprets it contextually based on historical analysis. At that time, women held a very weak position in society, casting doubts on their ability to lead a community institution. Additionally, they did not receive adequate education, resulting in limited experience and knowledge. Therefore, in the present era, if a woman has the capacity to be a leader, it is considered permissible. Keywords: Women’s Leadership, Muhammadiyah, Fatwa